Design and Validity of a Cognitive Conflict-Based Physics Educational Game to Support Students’ Conceptual Understanding of Rectilinear Motion Material - Rina Oktaviani; Fatni Mufit; Letmi Dwiridal; Fuja Novitra (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2025)
Understanding concepts is important in learning physics because it helps students connect theories with real-life phenomena, develop scientific reasoning, and avoid misconceptions. However, in practice, physics learning still faces challenges, especially in the topic of straight-line motion. One solution is an educational physics game based on cognitive conflict, which is expected to improve students' concept understanding and correct misconceptions. This research is a type of development research using the Plomp development model. The educational game developed is based on cognitive conflict and consists of four stages: 1) Activating prior knowledge and misconceptions, 2) Presenting cognitive conflict, 3) Discovering concepts and equations, and 4) Reflection. The validity results for the physics educational game are V = 90, which is in the very valid category, and the practicality results are 92.48, which is in the very practical category. Based on these results, it can be concluded that the physics educational game based on cognitive conflict for improving students' concept understanding in the topic of straight-line motion meets good validity criteria and can be used in the learning process as an interactive teaching material.